Synthesis and self-assembly of dumbbell shaped ZnO sub-micron structures using low temperature chemical bath deposition technique - Borade, P.; Joshi, K. U.; Gokarna, A.; Lerondel, G.; Walke, P.; Late, Dattatray J.; Jejurikar, S. M. (Materials Chemistry and Physics, 2016)
We report well dispersed horizontal growth of ZnO sub-micron structures using simplest technique ever known i.e. chemical bath deposition (CBD). A set of samples were prepared under two different cases A) dumbbell shaped ZnO grown in CBD bath and B) tubular ZnO structures evolved from dumbbell shaped structures by dissolution mechanism. Single phase wurtzite ZnO formation is confirmed using X-ray diffraction (XRD) technique in both cases. From the morphological investigations performed using scanning electron microscopy (SEM), sample prepared under case A indicate formation of hex bit tool (HBT) shaped ZnO crystals, which observed to self-organize to form dumbbell structures. Further these microstructures are then converted into tubular structures as a fragment of post CBD process. The possible mechanism responsible for the self-assembly of HBT units to form dumbbell structures is discussed. Observed free excitonic peak located at 370 nm in photoluminescence (PL) spectra recorded at 18 K indicate that the micro/nanostructures synthesized using CBD are of high optical quality. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Electron microscopy (STEM; Microstructure; Nanostructures; Optical properties; Photoluminescence spectroscopy; Raman spectroscopy and scattering; TEM and SEM)

Utilization of waste biomass for the synthesis of functionalizable support for covalent anchoring of active organo catalyst - Doke, D. S.; Advani, J. H.; Naikwadi, D. R.; Gawande, M. B.; Walke, P.; Umbarkar, S. B.; Biradar, A. V. (ACS Sustainable Chemistry & Engineering, 2019)
A single step synthetic procedure for carbon microspheres from agricultural waste residue (sugarcane bagasse) by low-temperature hydrothermal carbonization using oxalic acid as a hydrating/dehydrating agent is developed. The FTIR and XPS spectroscopy analysis indicates the presence of −OH, −COOH, and C═O functional groups on the surfaces of carbon spheres. These functional groups of the carbon spheres were utilized as a novel route to anchor 3-aminopropyl-triethoxysilane and 3-(2-aminoethylamino)propyl)-trimethoxysilane via condensation of triethoxy/trimethoxy silanes for the synthesis of organo base supported on carbon catalysts. The catalytic activity of the obtained supported organo-base catalyst was demonstrated for C–C bond forming (Henry) reaction. Among all prepared catalysts, 3-(2-aminoethylaminopropyl)-trimethoxysilane grafted in toluene showed high conversion (up to 100%) of aldehydes with excellent selectivity toward β-nitrostyrene. The catalyst was reused five times without losing significant activity for the same reaction.